PENGARUH KECUKUPAN MODAL, RISIKO KREDIT DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA BANK UMUM SWASTA NASIONAL DI OJK - Jamilah, Imraatun; L. Tobing, Vargo Christian (LPPM Universitas Putera Batam, 2020)
This study purose to knowing capital adeqaucy, credit risk and liquidity on National Comercial Bank companies profitability whise registered with Financial Services Authority period 2015-2019. Data preferences in this study is secondary data such monetary quartal report National Commercial Foregin Exchange Bank companies and sampling method use purposive sampling method. Analysis method in this study using double linier regression, T test and F test. The conclusion of this research on partially capital adequacy have significant effect to profitability on significant value 0,000 < 0,05, credit risk have significant effect as partially to profitability on significant value 0,000 < 0,05 and liquidity as partially have negative effect and not significant to profitability on significant value 0,916 > 0,05. Simultantly capital adequacy, credit risk and liquidity have significant effect on profitability. Adjusted R square value such 4% and remaining 96% is explained by others variable not included in this research method.